Hypophyseal functions in the toad Bufo arenarum Hensel - Houssay, Bernardo A. (1949)
The study of the functions of the hypophysis of Bufo arenarum Hensel (and other batrachians) was started forty years ago in Argentina. This toad is perhaps the species in which the largest number of functions related to the hypophysis has been found and studied. The importance of this work lies in the general principle of endocrinology that hormonal actions have a fundamental similarity in all species.